Optimization of total phenolic content from Terminalia chebula Retz. fruits using response surface methodology and evaluation of their antioxidant activities - Sheng, Zunlai; Zhao, Jiahong; Muhammad, Ishfaq; Zhang, Ying (PloS one, 2018)
Ultrasonic-assisted extraction (UAE), using aqueous ethanol as the solvent, was firstly applied to extract phenolic compounds from Terminalia chebula Retz. fruits (T. chebula fruits). In this study, ethanol concentration (%), ultrasonic intensity (W/cm2), particle diameter (mm), extraction temperature (°C), ultrasonic time (min), liquid-solid ratio (mL/g) and extraction cycle were investigated by single-factor experiment and then optimized using a Box-Behnken design. The optimized result for UAE was 68% ethanol concentration, ultrasonic intensity of 3.6 W/cm2, solid-liquid ratio of 23 mg/mL, particle size of 0.18 mm and ultrasonic time of 20 min for 2 times at 70 °C. The yield of total phenolic was 448.7 ± 2.15 mg GAE/g DW under the above optimum conditions, which agreed with the predicted value (447.8 mg GAE/g DW). Compared to conventional solvent extraction (CSE), UAE extracts showed excellent DPPH radical, DPPH, ABTS scavenging activities and reducing power in a dose-dependent manner, and better than that of CSE extracts. Additionally, the extract of the T. chebula fruits was analyzed by HPLC-ESI/MS. In summary, UAE could effectively extract phenolic compounds from T. chebula fruits. In addition, the extract could be used as a potential source of natural antioxidants.